JELAJAH ARKEOLOGI DAN MEMBACA PESAN-PESAN SEJARAH DARI KELAMPAUAN: SUATU PENELITIAN PENDAHULUAN - I Made Sutaba (BALAI ARKEOLOGI PAPUA, 2021)
Archaeological research in Indonesia until the present days, has successfully discovered a diverse historical and archaeological heritage, which are classified as cultural heritage. This cultural heritage is an advice and source of historical information of the past life of the pluralistic Indonesiain ancestor. This cultural heritage beared problems, namely the aspect of typology, sociology and ideology in its contextual relationship that are unlikely to study it now. This research concentrates on the subjects in its relationship to the historical of the past and its relevance to the future of the nation building that not yet studied before. This research is a preliminary study concerning the historical messages of the past. The purpose of this research is to find out the answer of the problems. This research is done through library study for collecting data and the analysis was carried out using typological approach. The result of this study indicater a significance messages are the historical counsciousness, sense of nationalism, and its fundamental relevance for building the future of Indonesian nation. So far it is impossible to get the complete historical messages and sense of nationalism due to it characters such as incomplete, fragile, finite and so on.